A Simple Method for Removal of the Distal Segment of a Broken Femoral Intramedullary Nail : A Case Report - Pan, K.L.; Reuben, P.R (Malaysian Orthopaedic Journal, 2012)
Broken locked intramedullary nail secondary to nonunion of the femur following radiotherapy for fibromatosis. A Kirschner wire with one tip fashioned into a hook was used to remove the distal segment without opening with the nonunion site. Details of the procedure are described.